Revising the Anticipated Success of Car Sharing Schemes: A Psychological Investigation into Car Owner's Materialistic and Attitudinal Values - Hoffmann, Christin (2012)
It is argued that the propensity to participate in car sharing schemes is very low and that the success which is being anticipated by economists and policy makers faces serious barriers. Based on findings from travel psychology, scarce literature about sharing itself and the nature of material possessions, the author conducted qualitative interviews amongst twelve car owners in the UK to deeply explore as to how far materialism, attitudes and habits act as barriers to sharing with regard to automobiles. These initial themes were proven to be important determinants whereby it was discovered that the routines of car use go beyond habitual processes but have rather taken the form of car reliance. Key findings further indicate that private car ownership is mainly due to societal structures and the mere pressure to own a car which is a phenomenon attributable to the prevalent car culture in the UK. Furthermore, when trying to predict the inclination to share, the study revealed that person-situation and gender differences are variables that need to be considered but have rather been neglected by literature surrounding travel psychology. Lastly, it was found that an absence in environmental concerns further lowers the propensity to participate into car sharing systems.